TANGGAPAN PENGGUNA PINJAMAN ONLINE DITINJAU DARI ELABORATION LIKELIHOOD MODEL - Hidayati, Ratih Kurnia; Akbar, Ananto; Irwandy, Deddy (Universitas Islam Syekh Yusuf, 2024)
Online loans have become a popular phenomenon in the modern financial sector, allowing individuals to obtain additional funds quickly and easily without complicated procedures at banks. Despite its convenience, online lending also faces challenges such as the risk of fraud, lack of financial understanding and the problem of missed payments. This article discusses the growth of online lending in Indonesia, starting with the emergence of Financial Technology (fintech) companies that combine finance with information technology. The Financial Services Authority (OJK) notes that most online loans are used for financing Micro, Small and Medium Enterprises (MSMEs). However, there is also the phenomenon of online loans that cause problems in society. Financial education is crucial in improving people's understanding of finance and managing online loans responsibly. In recent years, the use of debt to meet the needs of life has increased, but self-control in borrowing decisions is affected by the supply side. In conclusion, it is important to understand both the benefits and risks of online lending and the importance of financial literacy in managing personal finances.